Long-Term Aortic Remodeling After Thoracic Endovascular Aortic Repair of Acute, Subacute, and Chronic Type B Dissections - Li, Zhenjiang; Wang, Xiaohui; He, Yangyan; Xiang, Yilang; Wu, Ziheng; Zhang, Hongkun; Li, Donglin (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aimed to investigate the characteristics and predictors of aortic remodeling over a long-term follow-up period after thoracic endovascular aortic repair (TEVAR) for acute, subacute, and chronic type B aortic dissections (TBADs). Methods Patients who underwent TEVAR for TBAD from July 2011 to December 2013 were included, and relevant data were retrospectively analyzed. Results After TEVAR, the true lumen (TL) dimension increased and the false lumen (FL) dimension decreased or did not change over a 5-year follow-up period in all three temporal groups. Shrinkage proportion of the thoracic aorta was the highest in the subacute group (acute, 28.1%; subacute, 39.1%; and chronic, 17.4%; p = 0.048), while abdominal expansion showed no significant differences among the groups (acute, 29.6%; subacute, 40.5%; and chronic, 44.4%; p = 0.502). The chronic group had a rate of complete FL regression, which is lower than the subacute or acute group at all anatomic sections, with significant differences only in the stented section (chronic, 21.7%; acute, 92.2%; and subacute, 80.4%; p < 0.05) and in the distal thoracic aortic section (chronic, 13.0%; acute, 31.1%; and subacute, 50.0%; p < 0.05). Logistic regression analysis demonstrated that chronic dissection, TL compression, endoleak, the number of branches from FL, and the number of residual tears affected optimal FL remodeling. Conclusion The present study provides data on aortic remodeling of TBAD after TEVAR during a long-term follow-up period. The features and risk factors of aortic remodeling in the acute, subacute, and chronic phases are different in different aortic segments. These findings may have implications in the timing of TEVAR.